Pengaruh Halal Awareness, Islamic Branding, Perceived Quality dan Harga Terhadap Niat Membeli Produk Kosmetik Wardah - Lisa Nurhanifah; Luqman Hakim Handoko; Fahmi Syahbudin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to determine the influence of Halal Awareness, Islamic Branding, Perceived Quality, and Price on Wardah Cosmetic Product Purchase Intention among female STEI SEBI students. The research method used is research with a quantitative approach and the data analysis tool used is SmartPLS version 4.0. The sample for this research were active female students from the Classes of 2020, 2021, 2022, and 2023 who have used or are currently using Wardah cosmetic products. The tool used to obtain respondent data is a Google form questionnaire. The sample selection used purposive sampling with the number obtained were 100 respondents. The results of this research state that partially the Islamic Branding and Price variables have a significant effect on Purchase Intention, while Halal Awareness and Perceived Quality do not have a significant effect